Biotin plays an important role in Arabidopsis thaliana seedlings under carbonate stress. (November 2020) - Wang, Yao; Wang, Min; Ye, Xiaoxue; Liu, Hua; Takano, Tetsuo; Tsugama, Daisuke; Liu, Shenkui; Bu, Yuanyuan
Highlights: We investigated the effects of exogenously applied biotin on Arabidopsis growth under carbonate stress. We measured the endogenous biotin content and the expression of AtBIO2 in Arabidopsis in response to carbonate treatments. The phenotypes of wild-type, AtBIO2 -overexpressing, and bio2 mutant plants exposed to carbonate stress were compared. We analyzed the accumulation of reactive oxygen species as well as antioxidant enzyme activities. We combined two so far seemingly unrelated properties and confirmed that biotin responds to carbonate stress in plants. Abstract: Globally, many saline-alkali soils are rich in NaHCO3 and Na2 CO3, which are characterized by a high pH Carbonate stress caused by this kind of soil severely damages plant cells and inhibits plant growth. Biotin and HCO3 − participate in the first and rate-limiting reaction of the fatty acid biosynthesis pathway, but whether biotin contributes to plant responses to carbonate stress is unclear. In this study, we revealed that high carbonate and biotin concentrations inhibited Arabidopsis ( Arabidopsis thaliana ) seedling growth. However, specific concentrations of carbonate and biotin decreased the inhibitory effects of the other compound at the germination and seedling stages. Additionally, a carbonate treatment increased the endogenous biotin content and expression of AtBIO2, which encodes a biotin synthase. Moreover, phenotypic analyses indicated that the overexpression of AtBIO2 in Arabidopsis enhanced the tolerance to carbonate stress, whereas mutations to AtBIO2 had the opposite effect. Furthermore, the carbonate stress-induced accumulation of reactive oxygen species was lower in plants overexpressing AtBIO2 than in the wild-type and bio2 mutants. Accordingly, biotin, which is an essential vitamin for plants, can enhance the resistance to carbonate stress.